2004
DOI: 10.1007/s00464-004-8112-x
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of reuse of disposable laparoscopic instruments in laparoscopic cholecystectomy: a prospective randomized study

Abstract: This study showed that reusing DLI did not change the operative and postoperative outcomes or the infection rate for laparoscopic cholecystectomy when strict rules for disinfection were followed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0
5

Year Published

2004
2004
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 13 publications
(16 reference statements)
0
26
0
5
Order By: Relevance
“…In some cases, clinical trials are performed to evaluate the safety and effectiveness of reusing SUDs [21,22]. However, most studies involve laboratory experiments designed either to evaluate the efficacy of different sterilization methods [23][24][25] or to study the effects of reprocessing on the material properties (e.g., tensile strength) of devices [26][27][28].…”
Section: Relevant Literaturementioning
confidence: 99%
“…In some cases, clinical trials are performed to evaluate the safety and effectiveness of reusing SUDs [21,22]. However, most studies involve laboratory experiments designed either to evaluate the efficacy of different sterilization methods [23][24][25] or to study the effects of reprocessing on the material properties (e.g., tensile strength) of devices [26][27][28].…”
Section: Relevant Literaturementioning
confidence: 99%
“…13,14,16,27 Evidence of the clinical significance of residual contamination or mechanical failure reported in vitro is lacking, however, and other reports have indicated that reuse of certain disposable devices is safe, ethical, and cost-effective. 12,[28][29][30][31] By subjecting this disposable port and its components to repeated cycles of simulated use, decontamination, and sterilization, our goal was to mimic the physical fatigue experienced by the port in a clinical setting. We have demonstrated that VHP is effective at eliminating bacteria from the ports despite the physical fatigue that may occur with multiple uses.…”
Section: Discussionmentioning
confidence: 99%
“…For example ERCP accessories, angiography guidewires, and even disposable laparoscopic instruments have been reused after proper sterilization without detrimental effect in terms of increased the risk of infection. [2730]…”
Section: Discussionmentioning
confidence: 99%